PTH-041 Large (<4 cm) and giant (≥4 cm) colorectal polyps: comparison of piecemeal resection outcomes. (22nd June 2015) - Tsiamoulos, ZP; Elliott, T; Rameshshanker, R; Suzuki, N; Peake, S; Bourikas, L; Saunders, BP
Abstract : Introduction: Piecemeal Endoscopic Mucosal Resection (p-EMR) is a standard and safe endoscopic technique for resection of large colorectal polyps (>2 cm). Limited data are available regarding p-EMR of giant polyps (>4 cm). Method: A prospective study recording short and long-term outcomes after p-EMR for colorectal polyps > 2 cm between Jan 2010 and August 2012 was conducted. We compared two cohorts of patients: group-A with large polyps (2 to <4 cm) vs group-B with giant (≥4 cm) polyps. Chi-square/Fischer's tests were performed between categorical variables including patient demographics/polyp features/techniques applied p-EMR with spiral snare and hybrid p-EMR). Our primary outcome was to compare the safety, efficacy and complication rate between the two groups. Results: Group-B patients were older than group-A patients (mean 70.6 vs. 67.8 yrs